PERANCANGAN PROTOTYPE USER INTERFACE APLIKASI MOBILE TOKO KUE AZEL MENGGUNAKAN METODE DESIGN THINKING - Harlina, Masimbangan Sabarina; Susilowati, Eel; -, Suharni; Herawati, Masimbangan Susana; Zamzani, Azzalia Zahra (JURNAL REKAYASA INFORMASI, 2024)
Azel Cake Shop is a food business that promotes and sells its products still utilizing limited information technology media, namely via WhatsApp social media, This causes promotion and sales to not be optimal so that consumer reach does not meet expectations.With the creation of the User Interface and User Experience of the Azel Cake Shop mobile application with Prototype-based to help cake shop owners market their products widely, provide information about available products or pre orders├é┬╕ and can help consumers to buy cakes easily through the application. UI/UX design based on mobile applications for Azel Cake Shop with Prototype using Design Thinking Method.. The five stages of the Design Thinking Method are: Empathize, Define, Ideate, Prototype, dan testing. At this prototyping stage, the mobile application design will be displayed in wireframe form. Next, test the prototype using Maze with five tasks and five feedback. Based on the test results using Maze, it shows that the application that has been created can be used/accessed well with the features available in the application. his means that there are no tasks that are difficult to do. In this way, the prototyping of the Azel Cake Shop mobile application can help consumers to buy cakes easily and efficiently and can be used as promotional media. Keywords: Prototype. Mobule Application, Design Thinking, UI/UX. Design.